Molecular dynamics simulation and free energy calculation studies of the binding mechanism of allosteric inhibitors with TrkA kinase. Issue 1 (2nd January 2021) - Wu, Xiaoyun; Li, Qinlan; Wan, Shanhe; Zhang, Jiajie
Abstract: Tropomyosin receptor kinase A (Trk A) is a receptor tyrosine kinase activated by nerve growth factor (NGF). TrkA plays an important role in pain sensation, which leads to significant interest in the development of small molecule inhibitors of TrkA. However, TrkA and the other two highly homologous isoforms, TrkB and TrkC, are highly conserved in the ATP binding site, which suggests that achieving TrkA subtype selectivity over TrkB and TrkC in this site may be extremely challenging. Allosteric inhibitors without making any interactions with the conserved ATP binding site may present a more promising approach. Recently, selective TrkA inhibitors 1 and 2 were reported to be allosteric inhibitors targeting the DFG-out allosteric pocket. In the present study, molecular dynamics simulations and free energy calculations were carried out on TrkA in complex with ligands 1 and 2, which was expected to provide a basis for the rational drug design of TrkA allosteric inhibitors.